Lexical Analysis of Oral Discourse Among Young Spanish-Speaking Gamers: The Case of Minecraft - Luján-García, Carmen (Complutense Journal of English Studies, 2025)
The presence of video games is notable and currently constitutes one of the means of socialization among Spanish-speaking youth. This article analyzes the impact that some gamer YouTubers, who create content related to the world of video games, currently have. Based on a selection of Minecraft videos from three gamer YouTubers with millions of subscribers, the type of language they use will be examined. On the one hand, the considerable use of anglicisms and the formation of anglicized neologisms will be examined. On the other hand, the study will delve into the specialized nature of the language they use while playing Minecraft. The results reveal that the use of non-adapted anglicisms and neologisms is very frequent in the oral discourse of gamers. Furthermore, the use of specialized terminology or jargon is evident, contributing to fostering a sense of belonging within the Minecraft player community. Many of the lexical units examined fulfil different pragmatic functions in discourse: referential, expressive, and textual.